2022
DOI: 10.1093/mtomcs/mfac047
|View full text |Cite
|
Sign up to set email alerts
|

The zinc proteome of SARS-CoV-2

Abstract: Zinc is an essential element for human health. Among its many functions, zinc(II) modulates the immune response to infections and, at high concentrations or in the presence of ionophores, inhibits the replication of various RNA viruses. Structural biology studies on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) revealed that zinc(II) is the most common metal ion that binds to viral proteins. However, the number of zinc(II)-binding sites identified by experimental methods is far from exhaustive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…Aer being infected with SARS-CoV-2, we observed an evident decrease of multiple metal(loid)s (Se, Zn, Ca, Mg, K, I, Cr and Mo) in COVID-19 patients, among which some metal(loid)s e.g., Se, Zn, even show signicant variations with disease severity. It is reported that multiple metal ions, e.g., Zn 2+ , 27,28 are critical cofactors of many viral enzymes, proteases and polymerases that aid in viral replication and are required for proper functions of several non-structural proteins in SARS-CoV-2. The disturbance of the metabolism of these metals may result from the competition of essential elements between virus and hosts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aer being infected with SARS-CoV-2, we observed an evident decrease of multiple metal(loid)s (Se, Zn, Ca, Mg, K, I, Cr and Mo) in COVID-19 patients, among which some metal(loid)s e.g., Se, Zn, even show signicant variations with disease severity. It is reported that multiple metal ions, e.g., Zn 2+ , 27,28 are critical cofactors of many viral enzymes, proteases and polymerases that aid in viral replication and are required for proper functions of several non-structural proteins in SARS-CoV-2. The disturbance of the metabolism of these metals may result from the competition of essential elements between virus and hosts.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that multiple metal ions, e.g. , Zn 2+ , 27,28 are critical cofactors of many viral enzymes, proteases and polymerases that aid in viral replication and are required for proper functions of several non-structural proteins in SARS-CoV-2. The disturbance of the metabolism of these metals may result from the competition of essential elements between virus and hosts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc is a vital element for the proper function of our immune system against infections acting as an immunomodulator and inhibiting viral replication [ 23 ]. Studies have highlighted the role of zinc in COVID-19 as being the main ion that binds to SARS-CoV-2 through several zinc-binding sites recognized through proteomic analysis of the virus [ 24 ]. These studies have evidenced the binary effect of zinc on SARS-CoV-2, as its binding can prove both fundamental for viral reproduction as well as toxic.…”
Section: Discussionmentioning
confidence: 99%
“…The latter tool, called MetalS 3 , is available as a web server at (accessed on 5 July 2022) [ 56 ]. As an example, in a recent application we used MetalS 3 to investigate systematically the similarities between the zinc(II)-proteome of SARS-CoV-2 and known metalloprotein structures, uncovering the fact that the large majority of viral MBSs are close to eukaryotic zinc(II) sites [ 57 ].…”
Section: Structural Comparison Of the Metal Sitesmentioning
confidence: 99%